PRESPEKTIF HAKIM TERHADAP REGULASI HUKUM DAN PROFESIONALISME, MEKANISME DAN BIAS PENGAMBILAN KEPUTUSAN HAKIM DALAM PENANGANAN KASUS PERMOHONAN SUAMI IJIN POLIGAMI PADA PENGADILAN AGAMA SUMBER DI KABUPATEN CIREBON - Abdul Fatakh; Wasman Wasman (UIN Siber Syekh Nurjati Cirebon, 2021)
ABSTRAC ABSTRACTPolygamy, which is permitted by positive law and Islamic law, is merely a justice for the rights of both human beings which is demanded between the masculine and the feminine, so that the goal is sakinah mawaddah warahmah. The practice of polygamy has experienced deviations by some people (men/husbands) resulting in fatal consequences for the portrait of justice, especially for women/wives. many polygamists do not get permission for polygamy from the Religious Courts, the practice of polygamy mostly results in divorce and exploitation of the rights of wives, and children, compared to polygamy that gets permission from the Religious Courts, which has very little impact on divorce.Based on the description, so doing research with the formulation of the problem: the perspective of the professionalism of judges and the mechanism of judge decision-making in handling cases of husband's application for polygamy permission at the religious court in Cirebon, How is the Legal Regulation of Professionalism Decisions of Religious Court Judges in Cirebon Regency against the mechanism of Licensing and Rejection of Polygamy in Cirebon. ask husbandFrom the results of data analysis, it can be concluded that the Legal Regulations on Professionalism Decisions of Religious Court Judges in Indonesia Against the mechanism for Licensing and Rejection of Polygamy proposed by husbands, namely: Law Number 1 of 1974 Articles 4 and 5, and Compilation of Islamic Law Articles 55-59, and judges are required to carry out legal excavations while still within the material legal framework of polygamy law;The perspective of the professionalism of judges and the judge's decision-making mechanism in handling cases of husband's application for polygamy permission at a religious court in Indonesia, namely the judge's view of the status of polygamous marriages which is based on permission from the Religious Courts and illegal polygamy, does not have the authority to determine the legal status or not of marriage unless the case is brought to the Religious Court, the judge will only know the legal status of the polygamous marriage. And judges in the trial for the decision-making process on polygamy permits, judges use the procedural law of the Religious Courts, referring to book II of judges' guidelines on administrative and technical technicalities of Religious Courts, chapter on special guidelines for family law on polygamy, material law on polygamy as the legal basis and mandatory judges carrying out legal excavation must not be outside the material law. Keyword: Judge's Perspective, Legal Regulation, Polygamy Permit, Cirebon Regency Religious Court ABSTRAKPoligami yang diperbolehkan secara hukum positif dan hukum Islam, semata-mata hanya sebuh keadilan hak bagi kedua mahluk insan yang di tuntutnya antara kaum maskulin dan feminim, agar tujuannya sakinah mawadah warahmah. Praktek poligami telah mengalami penyimpangan oleh sebagian masyarakat kaum (laki-laki/suami) berakibat fatal bagi potret keadilan, khususnya ini dirasakan bagi perempuan/isteri. banyak poligami tidak mendapatkan ijin poligami dari Peradilan Agama, praktek poligami ini sebagian besar berjung pada perceraian dan eksploitasi hak-hak isteri-isteri, dan anak-anak, dibanding poligami yang mendapatkan ijin dari Peradilan Agama, yang sangat sedikit sekali yang dampaknya perceraian.Berdasarkan uraian, sehingga melakukan penelitian dengan rumusan permasalahan: prespektif profesionalisme Hakim dan mekanisme pengambilan keputusan hakim dalam penanganan kasus permohonan suami ijin poligami pada pengadilan agama di Cirebon, Bagaimana Regulasi Hukum Keputusan Profesionalisme Hakim Pengadilan Agama di Kabupaten Cirebon Terhadap mekanisme Perijinan Dan Penolakan Poligami yang di ajukan suamiDari hasil analisis data dapat disimpulkan, Regulasi Hukum Keputusan Profesionalisme Hakim Pengadilan Agama di Indonesia Terhadap mekanisme Perijinan Dan Penolakan Poligami yang di ajukan suami yaitu: Undang-undang Nomor 1 tahun 1974 Pasal 4 dan 5, dan Kompilasi Hukum Islam Pasal 55-59, dan hakim diwajibkan melakukan Penggalian hukum selagi masih dalam bingkai hukum materiil hukum poligami;Prespektif profesionalisme hakim dan mekanisme pengambilan keputusan hakim dalam penanganan kasus permohonan suami ijin poligami pada pengadilan agama di Indonesia, yaitu pandangan hakim terhadap status perk awinan poligami yang dilatar belakangi ijin dari Peradilan Agama dan poligami liar, tidak mempunyai wewenang untuk menentukan status sah dan tidaknya perkawinan tersebut, kecuali kalau perkara tersebut dibawa ke Pengadilan Agama, Hakim baru mengetahui status sah tidaknya perkawinan poligami tersebut. Dan hakim dalam persidangan untuk proses Pengambilan Keputusan terhadap ijin poligami, hakim menggunakan hukum acara Peradilan Agama, merujuk pada buku II pedoman hakim tentang teknis administrasi dan teknis Peradilan Agama bab Pedoman khusus hukum keluarga tentang poligami, hukum materiil tentang poligami sebagai dasar hukumnya dan hakim wajib melakukan penggalian hukum tidak boleh keluar dari hukum materiil; Keyword: Prespektif Hakim, Regulasi Hukum, Ijin Poligami, Pengadilan Agama Kabupaten Cirebon